Ferric sodium edetate therapy in children with iron deficiency anemia - Christie Moningkey; Max F.J. Mantik; Vivekenanda Pateda (Paediatrica Indonesiana, 2015)
Background Iron deficiency anemia (IDA) is frequentlyfound in school-aged children. The main treatments for IDAare overcoming the causal factors and iron supplementation.Noncompliance in taking iron tablets and the possibility of ironabsorbtion or transport difficulties, can reduce efficacy of daily oraliron supplementation. Because excess iron storage in the intestinalcells can lead to mucosal blockage, twice weekly oral iron therapymay be considered instead of daily dosage.Objective To compare the effects of daily vs. twice weekly ferricsodium edetate (NaFeEDTA) on hemoglobin (Hb), hematocrit(Ht), mean corpuscular volume (MCV), mean corpuscularhemoglobin (MCH), and mean corpuscular hemoglobinconcentration (MCHC) levels on children with IDA.MethodsWe conducted an open-label, randomized, prospectivestudy in 36 children with IDA aged 5-11 years. Subjects weredivided into two groups. For a one-month period, group I receiveddaily iron therapy (NaFeEDTA) and group II received twiceweekly iron therapy. Examinations of Hb, Ht, MCV, MCH, MCHCwere performed before and after iron therapy.Results There were no significant differences in Hb, Ht, MCV,MCH or MCHC levels after therapy between the daily and twiceweekly NaFeEDTA groups (P > 0.05).Conclusion Twice weekly NaFeEDTA therapy is as effective asdaily NaFeEDTA administration in children with IDA.